Dampak Latihan Drop shot Target Statis dan Dinamis terhadap Akurasi Pukulan Drop shot pada Siswa Ekstrakurikuler Bulutangkis SD Negeri Sumbaga 02 - Suroso Suroso; Didi Muhtarom (Jurnal Pendidikan Dirgantara, 2026)
This study aims to determine the effect of fixed target and changing target drop shot training, as well as to examine the difference in effectiveness between the two methods on drop shot accuracy among badminton extracurricular participants at SD Negeri Sumbaga 02. This study employed a quantitative approach with a quasi-experimental method and a non-equivalent control group design. Sampling was conducted using a purposive sampling technique, resulting in 30 students, equally divided into a fixed target group (n=15) and a changing target group (n=15). The data collection instrument used a modified French Drop shot Test that had been validated with a feasibility level of 92.5%. Data analysis was performed using SPSS, including prerequisite tests and hypothesis testing (Paired T-Test, Independent T-Test, and N-Gain). The results showed that both methods had a significant effect on improving drop shot accuracy with a significance value of 0.000 < 0.05. However, the Independent Sample T-Test results indicated a highly significant difference in effect between the two groups (Sig. 0.000 < 0.05). N-Gain analysis corroborated these findings, where the changing target training group recorded an effectiveness of 68.57% (medium approaching high category), far superior to the fixed target training group which only reached 33.96% (medium category). The conclusion of this study is that changing target training is proven to be more effective and is recommended for improving students' drop shot accuracy compared to fixed target training which tends to be monotonous.